Business Plan for The Development of Triple D Boarding House: Establishing A One-Stop Shopping Ecosystem - Cecep Supriadi; Meriza Hendri (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
The boarding house business is a rapidly growing property sector in Indonesia's urban areas, driven by a high urbanization rate that saw the urban population increase to 56.7% by 2022, and the concentration of educational and office centers. Bandung, as a major educational city with over 305,000 active students and an estimated market potential reaching IDR 1.53 trillion annually, has become a strategic and attractive location for investors. This trend is further amplified by a digital shift, with reports indicating that 72% of tenants in Bandung now use online platforms to find accommodation. However, this industry faces challenges from intense competition, rising consumer expectations for adequate facilities, and a market shift towards housing that is not only functional but also supports a productive and community-oriented lifestyle. This study aims to develop a business plan for the expansion of Triple D Kos by opening a new branch with a "One Stop Shopping Ecosystem Business" concept. The analysis was conducted through an internal and external business environment approach using the Porter's Five Forces framework, strategy formulation using the Lean Canvas, and complemented by a feasibility study based on entrepreneurial aspects of the Timmons Model and financial analysis (NPV, IRR, Payback Period, Profitability Index). The results show that despite a high threat of new entrants and strong bargaining power of buyers, significant opportunities exist through service differentiation by providing integrated facilities. The recommended strategies include developing housing with a value-added ecosystem, strengthening digital-based marketing, and implementing efficient operational management to increase tenant loyalty. Theoretically, this research enriches the entrepreneurship literature on the application of strategic models in the boarding house industry. Practically, this business plan provides a comprehensive investment and operational guide for Triple D Kos to enhance its competitiveness, expand its market share, and achieve sustainable business growth.